2009
DOI: 10.3109/00016340903322743
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of early serum β‐hCG levels after single blastocyst transfer

Abstract: The predictive value of a single beta-hCG measurement for pregnancy outcome after single blastocyst transfer increases between days 11 and 21 after OR. A single beta-hCG measurement on day 14 may balance the accuracy of prediction and the necessity of an early reassuring test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…[8] There has been published data on serum HCG as a predictor of pregnancy outcome from the western countries. [56] We present our data from the developing country in the Asian population. This is a retrospective study analyzing data in 139 patients with IVF conception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] There has been published data on serum HCG as a predictor of pregnancy outcome from the western countries. [56] We present our data from the developing country in the Asian population. This is a retrospective study analyzing data in 139 patients with IVF conception.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of serum HCG levels on day 14 of ET has good sensitivity and specificity to predict pregnancy outcome in terms of viable and non-viable pregnancies. [567]…”
Section: Introductionmentioning
confidence: 99%
“…HCG is of placental origin, represents trophoblast functional integrity, and appears in maternal blood approximately 6 to 8 days after fertilization. Numerous studies have revealed that pregnancies with low initial hCG values are associated with a poor prognosis [2-6]. Serum hCG levels at 11 days post-ET are significantly lower for those that experience early pregnancy loss, and a cut-off of 50 mIU/mL was found to predict pregnancy outcome with good sensitivity and specificity of 75% and 81%, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive predictive value (PPV) of hCG at this cut-off level was around 50% and its negative predictive value (NPV) was 93% in those study. However, in two recent studies, with cut-off values of 80 and 76 mIU/mL, the PPV of hCG was 93.3% and 87% and NPV was 40% and 74%, respectively [2,3]. …”
Section: Introductionmentioning
confidence: 99%
“…Most studies that evaluate early maternal serum hCG measurements and outcome are performed in an IVF setting (7)(8)(9)(10)(11)(12). The specific advantages of this population include accurate pregnancy dating and meticulous early pregnancy surveillance.…”
mentioning
confidence: 99%